Pruebas de sensibilidad para Mycobacterium tuberculosis - Ugarte Gil, César (2020)
Inadequate treatment regimens and poor compliance have led to increased rates of drug resistance in Mycobacterium tuberculosis around the world, leading to the emergence of multidrug resistant (MDR) and extensively drug resistant (XDR) strains. In Peru MDR-TB rates are amongst the highest in the world and XDR-TB cases have been reported for almost a decade. Drug susceptibility tests detect cases with resistant strains, providing the best treatment option to the patient and diminishing the spread of the disease. This review is directed at the non-specialist physician, focusing upon the drug susceptibility tests approved by the National TB Program of Peru and others currently still under research.